(untitled) (Communications in Computational Physics, 2020)
In the present work two component dense semiclassical plasma of protons and electrons is considered. Microscopic and electrodynamic properties of the plasma by molecular dynamic simulation are investigated. For these purposes semiclassical interparticle potential which takes into account quantum mechanical diffraction and symmetry effects is used. The considered range of density of plasma is n=1022cm−3 to n=1024cm−3. Fluctuations and dynamic dielectric functions were calculated using velocity autocorrelation functions.